Individual and contextual determinants of adoption of online media services in the 2017 lower house election campaign in Japan. (July 2020) - Vergeer, Maurice; Tkach-Kawasaki, Leslie; Lee, Junku
Highlights: Candidates adopted online media services in a consistent order (range: easy-difficult to operate); MCA and Mokken analysis are useful scaling techniques to measure adoption of technology; Individual and contextual characteristics both explain adoption of online media services; Candidates on the PR list adopted more online media services than those in districts; Incumbent candidates adopted more online media than new and former candidates; Younger candidates adopt more online media for campaigning than older candidates. In densely populated areas, candidates adopted more online media services for campaigning.